2014
DOI: 10.1016/j.bbadis.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The lipid flippase heterodimer ATP8B1–CDC50A is essential for surface expression of the apical sodium-dependent bile acid transporter (SLC10A2/ASBT) in intestinal Caco-2 cells

Abstract: Deficiency of the phospholipid flippase ATPase, aminophospholipid transporter, class I, type 8B, member 1 (ATP8B1) causes progressive familial intrahepatic cholestasis type 1 (PFIC1) and benign recurrent intrahepatic cholestasis type 1 (BRIC1). Apart from cholestasis, many patients also suffer from diarrhea of yet unknown etiology. Here we have studied the hypothesis that intestinal ATP8B1 deficiency results in bile salt malabsorption as a possible cause of PFIC1/BRIC1 diarrhea. Bile salt transport was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
(62 reference statements)
0
31
1
Order By: Relevance
“…For example, the functional role of cyclic GMP-dependent protein kinase II (cGKII) in ion transport was contradictory between T84 cells (no cGKII involvement) 22 and mouse intestine (cGKII is involved in fluid homeostasis) 23 . Another marked difference has been reported for the bile salt transporter ASBT between Caco-2 cells and mouse intestine 24 . Although not fully understood, ASBT might be regulated by differing mechanisms or differing P-type ATPases in Caco-2 cells and mouse intestine.…”
Section: Limitations Of Traditional Intestinal Modelsmentioning
confidence: 86%
“…For example, the functional role of cyclic GMP-dependent protein kinase II (cGKII) in ion transport was contradictory between T84 cells (no cGKII involvement) 22 and mouse intestine (cGKII is involved in fluid homeostasis) 23 . Another marked difference has been reported for the bile salt transporter ASBT between Caco-2 cells and mouse intestine 24 . Although not fully understood, ASBT might be regulated by differing mechanisms or differing P-type ATPases in Caco-2 cells and mouse intestine.…”
Section: Limitations Of Traditional Intestinal Modelsmentioning
confidence: 86%
“…Furthermore and in contrast to Chen and colleagues, Cai et al [17] and Van der Mark et al [23] have shown that ATP8B1 depletion in Caco-2 cells and human and rat hepatocytes leaves FXR activity unaffected.…”
Section: Atp8b1 Deficiency Causes Intrahepatic Cholestasis In Mice Anmentioning
confidence: 95%
“…Van der Velden et al [24] observed that knockdown of ATP8B1 in Caco-2 cells led to a loss in microvilli, an unorganized apical actin cytoskeleton and a posttranscriptional defect in apical protein expression. Van der Mark et al [23], on the other hand, showed that ATP8B1 depletion in Caco-2 cells resulted in impaired membrane insertion and consequent absence of the apical sodium-dependent bile acid transporter (ASBT/SLC10A2) from the apical membrane, without a change in cellular morphology. These discrepant findings may be attributed to artifacts introduced by clonal selection of cells, use of different Caco-2 cell clones, variation in culture conditions or combinations of these factors.…”
Section: Atp8b1 Deficiency Causes Intrahepatic Cholestasis In Mice Anmentioning
confidence: 99%
“…This finding may explain some of the extrahepatic symptoms of patients with PFIC1, such as hearing loss and diarrhea (91,95,99). Verhulst et al (76) reported that knockdown of ATP8B1 in Caco-2 cells led to loss of microvilli, and van der Mark et al (100) showed that ATP8B1 depletion did not affect the morphology of Caco-2 cells. Thus, it remains to be elucidated whether ATP8B1 is required for the formation of microvilli.…”
Section: Atp8b1mentioning
confidence: 99%